Challenges in Translating Humor and Idioms in Cartoons for Young Audiences - Turg’unova Irodaxon Xayrulla qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This article explores the unique linguistic and cultural challenges of translating humor and idiomatic expressions in animated cartoons intended for young audiences. Humor and idioms are powerful tools for emotional engagement and cultural learning but often resist direct translation due to their context-bound meanings. The article analyzes translation strategies, such as localization and cultural substitution, and emphasizes the need for age-appropriate adaptations that preserve the humor and educational value of the original. The goal is to highlight best practices for translators, educators, and media producers to ensure effective cross-cultural communication through children's animated content.